‘I always knew I would go to University’: a social realist account of student agency - Ellery, Karen; Baxen, Jean (South African Journal of Higher Education, 2016)
Academic development programs in higher education institutions in South Africa are often underpinned by discourses that view students as deficit. Margaret Archer’s social realist ontology offers a means of understanding reflexivities and agency of students in the higher education context. Using narrative data and drawing on Archer’s (2003) theory of mediation between structure and agency through internal conversations, this study examines the socio-economic background of one particular student and his agential journey to arrive at the academy. The analysis reveals Thando has a deliberate and determined stance towards achieving his project of obtaining a tertiary education in order to realize a better life for himself and his family. Despite what could be perceived as constraining socio-cultural conditions, Thando strategically circumvents such restrictions and acts in ways that help him pursue his project. It is argued that student agency needs to take a more central place within academic development programs in higher education.